Endothelial-Mesenchymal Transition in Heart Failure With a Preserved Ejection Fraction: Insights Into the Cardiorenal Syndrome. (September 2021) - Valero-Muñoz, María; Oh, Albin; Faudoa, Elizabeth; Bretón-Romero, Rosa; El Adili, Fatima; Bujor, Andreea; Sam, Flora
Abstract : Background: The management of clinical heart failure with a preserved ejection fraction (HFpEF) is often complicated by concurrent renal dysfunction, known as the cardiorenal syndrome. This, combined with the notable lack of evidence-based therapies for HFpEF, highlights the importance of examining mechanisms and targetable pathways in HFpEF with the cardiorenal syndrome. Methods: HFpEF was induced in mice by uninephrectomy, infusion of d -aldosterone (HFpEF; N=10) or saline (Sham; N=8), and given 1% NaCl drinking water for 4 weeks. Renal fibrosis and endothelial-mesenchymal transition (endo-MT) were evident once HFpEF developed. Human aortic endothelial cells were treated for 4 days with 10% serum obtained from patients with chronically stable HFpEF with the cardiorenal syndrome (N=12) and compared with serum-treated human aortic endothelial cells from control subjects (no cardiac/renal disease; N=12) to recapitulate the in vivo findings. Results: Kidneys from HFpEF mice demonstrated hypertrophy, interstitial fibrosis (1.9-fold increase; P <0.05) with increased expression of endo-MT transcripts, including pdgfrβ (platelet-derived growth factor receptor β), snail, fibronectin, fsp1 (fibroblast-specific protein 1), and vimentin by 1.7- ( P =0.004), 1.7- ( P =0.05), 1.8- ( P =0.005), 2.6- ( P =0.001), and 2.0-fold ( P =0.001) versus Sham. Immunostaining demonstrated co-localization of CD31 and ACTA2 (actin α2) in kidney sections suggesting evidence of endo-MT. Similar to the findings in HFpEF mice, comparable endo-MT markers were also significantly elevated in human aortic endothelial cells treated with serum from patients with HFpEF compared with human aortic endothelial cells treated with serum from control subjects. Conclusions: These translational findings demonstrate a plausible role for endo-MT in HFpEF with cardiorenal syndrome and may have therapeutic implications in drug development for patients with HFpEF and concomitant renal dysfunction.